New chapter for the South African Heart® Journal - Meel, Prof Ruchika (SA Heart Journal, 2024)
I hope this message finds you well. I would like to express my heartfelt gratitude for the opportunity to serve as the Editor of the SA Heart® Journal. I am truly honoured to take on this role and contribute to the advancement of cardiovascular research in our community. On behalf of the SA Heart® board I would like to thank the outgoing editorial team for their contributions to SA Heart® Journal. I look forward to collaborating with the esteemed editorial team and authors to uphold the Journal’s reputation for excellence. Together, I believe we can foster impactful research and insights that will benefit our readers and to the cardiology field.